Tinjauan Literatur: Penerapan E-Puskesmas di Indonesia: Penelitian - Diah Ratri Larasati; Cau Kim Jiu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The implementation of e-Puskesmas as a web-based information management system in primary healthcare facilities in Indonesia represents a crucial step toward improving service quality and effeciency. This literature review systematically examines five scientific articles published within the last six years, employing the PRISMA method along with inclusion and exclusion criteria. The search was conducted across academic platforms such as PubMed, Google Scholar, and Science Direct, utilizing the PIECES analytical framework. The findings indicate that e-Puskesmas accelerates administrative processes, facilitates patient data recording, and enhances transparency and service quality. However, challenges remain in the areas of control, efficiency, and economics, particularly concerning limited equipment availability, the need for human resource training, and internet connectivity stability. These findings underscore the importance of strengthening infrastructure, enhancing healthcare workforce capacity, and continuously developing the system to maximize the benefits of e-Puskesmas. In conclusion, e-Puskesmas holds significant clinical relevance in supporting the digital transformation of healthcare services, although improvements are still necessary to ensure optimal system performance across Indonesia.